The Influence of Tooth Primer and Zirconia Cleaners on the Shear Bond Strength of Saliva-Contaminated Zirconia Bonded with Self-Adhesive Resin Cement - Vorrawatn Pornatitanakul; Awiruth Klaisiri; Tool Sriamporn; Somporn Swasdison; Niyom Thamrongananskul (Applied Sciences)
This study investigated the effectiveness of Tooth Primer and cleaning agents in removing saliva contamination from zirconia as assessed using shear bond strength (SBS). A total of 175 rectangular specimens, 10 mm in diameter and 6 mm in thickness, were randomly divided into seven groups (n = 25 each): group 1, no saliva contamination (control); group 2, saliva-contaminated and not rinsed; group 3, saliva-contaminated and rinsed; group 4, saliva-contaminated, Ivoclean-treated, and rinsed; group 5, saliva-contaminated, Katana Cleaner-treated, and rinsed; group 6, saliva-contaminated, Tooth Primer-treated, and rinsed; and group 7, saliva-contaminated, Tooth Primer-treated, and not rinsed. All zirconia specimens from groups 1–7 were bonded to composite rods with Panavia SA Luting Multi cement. The bonded specimens were subjected to the SBS test using a universal testing machine. To assess the type of failure, the debonded surface was evaluated using a stereomicroscope. The SBS data were analyzed using one-way ANOVA with Tukey’s post-test. The SBS values of groups 2 (0.90 ± 0.20 MPa) and 3 (1.35 ± 0.43 MPa) were significantly lower compared with the other groups (p = 0.00). The SBS value of zirconia decontamination using Ivoclean in group 4 (18.51 ± 3.01 MPa) was significantly lower than that of the control group (22.24 ± 2.37 MPa) (p = 0.00). However, the SBS values of groups 5 (20.92 ± 2.63 MPa), 6 (21.43 ± 2.81 MPa), and 7 (20.87 ± 2.35 MPa) did not significantly differ compared with the control group (22.24 ± 2.37 MPa) (p = 0.369, p = 0.861, p = 0.327, respectively). Moreover, SBS values did not significantly differ among groups 5 to 7 (p = 0.984, p = 1.00, p = 0.976, respectively). Regarding failure mode, groups 2 and 3 exclusively experienced adhesive failures. Groups 1, 4, 5, 6, and 7 exhibited adhesive and mixed failures. In conclusion, Ivoclean, Katana Cleaner, and Tooth Primer effectively mitigated the adverse effects of saliva contamination on the resin cement–zirconia interface. Furthermore, Tooth Primer can be used as a cleaner for saliva-contaminated zirconia surfaces, with or without rinsing.